Strategic Planning of Infrastructure and Natural Resources in Urban Spatial Planning: Challenges and Solutions in the Era of Climate Change - YM, Hardiyanti; Sabriani, Sabriani; Sidabutar, Yuanita FD; Wenda, Notiben (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to explore the challenges and solutions in strategic planning of infrastructure and natural resources in Jayawijaya Regency, especially in the context of climate change. It was found that dependence on non-renewable energy sources contributes to climate change and disrupts energy supply. Proposed solutions include the development of renewable energy infrastructure, such as hydropower and solar energy, which can be integrated with sustainable natural resource management. Utilization of natural resources, such as air and sunlight, is expected to reduce carbon emissions and increase energy security. Spatial planning that considers energy networks is crucial to ensure accessibility and equitable distribution of energy throughout the region. Through this study, Jayawijaya Regency can not only face the challenges of climate change, but also create a more efficient and sustainable energy system, support economic growth, and improve the quality of life of the community.